Роль повітря в індукованому лазером тепловому випромінюванні поверхневих шарів поруватих вуглецевих матеріалів - Zelensky, S.E.; Kolesnik, O.S.; Yashchuk, V.P. (Publishing house "Academperiodika", 2023)
The influence of the surrounding air on the amplitude and shape of thermal radiation pulses (at a wavelength of 430 nm) during the heating of the surface layer of a porous carbon material (to temperatures of the order of 2000–3000 K) by the radiation of a Q-switched neodymium laser is studied. When the pressure of the surrounding air is reduced to forevacuum conditions, the experiments showed a one-and-a-half-fold increase in the amplitude of pulsed signals of thermal radiation and an increase in the decay time of the glow by about a third. Numerical calculations of the dynamics of the temperature field in the surface layer of the material during the irradiation by nanosecond laser pulses are carried out. An improved model is used in the calculations, which accounts for (i) the porosity of the material and (ii) the temperature dependence of the coefficients of thermal conductivity and the heat capacities of carbon and air. To calculate the thermal conductivity of the porous material, a model of a cubic array of intersecting square rods is used. The satisfactory consistency of calculation results with experimental data is obtained. The above-mentioned improvements of the calculation model made it possible to reconcile the estimates of the thermal characteristics of surface layers of carbon, obtained from the emission decay data, with the reference data published in the literature.